Impact of Submicroscopic Plasmodium falciparum Parasitaemia on Maternal Anaemia and Low Birth Weight in Blue Nile State, Sudan - Samia A. Omer; Ali N. Noureldein; Hadeel Eisa; Mutasim Abdelrahim; Hagir E. Idress; Abdelrahim M. Abdelrazig; Ishag Adam (Journal of Tropical Medicine)
The aim of the present study was to investigate the prevalence of submicroscopic infections and to assess its impact on maternal anaemia and low birth weight. A cross-sectional study was carried out with 1149 consented pregnant women who delivered at 3 main hospitals in the Blue Nile State, between January 2012 and December 2015. From a matched maternal peripheral, placental maternal side, and cord blood sample, blood films and dried spots were prepared for microscopic examination and nested polymerase chain reaction (n-PCR), respectively. 107 out of 447 negative blood films were found to have submicroscopic infection detected using n-PCR in any of the three compartments. Placental samples had a significantly higher prevalence (142) of submicroscopic infections compared with the peripheral (6.5%) and cord (8.1%) samples. The mean (SD) of the maternal haemoglobin (Hb) was significantly lower in cases with submicroscopic parasitaemia (10.9 (0.8) vs. 12.1 (0.7) g/dl, P<0.001) compared with those who had no submicroscopic parasitaemia. Submicroscopic malaria infection was associated with anaemia (OR 19.7, (95% CI, 10.3–37.8)). Thirty-eight babies born to women with submicroscopic infections were low birth weight (LBW) and was significantly lower in submicroscopic parasitaemia (2.663 (0.235) vs. 2.926 (0.341) kg, P<0.001). Submicroscopic malaria infection was associated with LBW (OR = 2.7, (95% CI, 1.2–5.6)). There is a high incidence of submicroscopic infections in any of the three compartments regardless of age or parity. Submicroscopic infection is a risk of maternal anaemia and low birth weight in women in this area of high seasonal malaria transmission.